The Palgrave Handbook of Innovative Community and Clinical Psychologies - Walker, Carl.; Zlotowitz, Sally; Zoli, Anna. (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2022)
This handbook highlights a range of ground breaking, radical and liberatory clinical and critical community psychology projects from around the world. The disciplines of critical community psychology and clinical psychology are currently experiencing radical innovations that in this book are characterised as moving from the individualising practice realm toward an altogether more contextualising orientation. Both fields are responding to an array of political, social and economic injustices and a global political context. Community and clinical psychologists have found themselves reorienting their practice to confront, resist and subvert the structures that are so damaging to the lives of the vulnerable people they work with. This text posits that these approaches refute and resist the psychologising that has strengthened oppressive structures. Such practices are starting to engage in the political character of power-knowledge relationships that demand a more 'action-oriented' and less 'clinical' psychology praxis and there is a growing interest in, and commitment to, social justice in the field of mental wellbeing. Using examples of scholar, activist and practitioner work from around the world, this collection explores and documents those practices where the traditional remits of community and clinical psychology have been subverted, altered, stretched, changed and reworked in order to reframe practice around human rights, creativity, political activism, social change, space and place, systemic violence, community transformation, resource allocation and radical practices of disruption and direct action. Carl Walker is a community psychologist at the University of Brighton and a borough councillor in Worthing, UK. He is on the British Psychological Society's Community Psychology section committee. Sally Zlotowitz is a clinical and community psychologist working in various roles including as Director of Public Health and Prevention at MAC-UK. She is past chair of the British Psychological Society's Community Psychology section and a co-founder of Psychologists for Social Change. Anna Zoli is a senior lecturer in Psychology, and course leader of the MA Community Psychology at the University of Brighton, UK. She is on the British Psychological Society's Community Psychology section committee, and a fellow of the Higher Education Academy (FHEA).
1. Introduction; Sally Zlotowitz, Carl Walker, Anna Zoli -- 2. Building alliances with marginalised communities to challenge London's unjust and distressing housing system; Nina Carey, Sally Zlotowitz, Samantha James, Aysen Dennis, Thomas Gillespie and Kate Hardy on behalf of The Housing & Mental Health Network -- 3. Growing a movement: Psychologists for Social Change; Psychologists for Social Change -- 4. Getting off the fence and steppin' outta the clinic room; The Walk the Talk Crew -- 5. Taking a position within powerful systems; James Randall, Sarah Gunn, Steven Coles -- 6. Supporting activists and progressive social movements; Tod Sloan, John Brush -- 7. Statactivism and Critical Community Psychology: using statistical activism to resist injustice in the NHS and Higher Education -- Carl Walker, Anna Zoli -- 8. Reflexively interrogating (de)colonial praxes in critical community psychologies; Nick Malherbe, Shahnaaz Suffla, Mohamed Seedat -- 9. Options: Conversation in Collaboration; Hannah Denton, Mark Haydon-Laurelut, M, Duncan Moss, Angela Paterson Foster, Jan Shepherd -- 10. Protesting against property foreclosures in a fragmentized socio-political sphere: an action-oriented model; Andreas Vavvos, Sofia Triliva -- 11. "We the Marlborough": elucidating users' experience of radical, informal therapeutic practices within a queer community pub; Charlotte Wilcox, Rebecca Graber -- 12. The Evolution of the Community Psychology Festival; Miltos Hadjiosif, Meera Desai -- 13. The Define Normal Project; Danny Taggart, Cheryl Nye, Jessica Taylor, Jacob Solstice, Matthew Harrison, Rebecca Bryant, Stacey Clark, Wendy Franks -- 14. Rewriting the space between a university and a healthcare provider: the model of Converge; Emma Anderson, Adam Bell, Paul Birch, Lucy Coleman, Paul Gowland, Matt Harper-Hardcastle, Eloise Ingham, Bekhi Ostrowska, Kev Paylor -- 15. The Jannah tree: An Islamic-faith inspired metaphor and spiritual framework for healing, co-created by British-Pakistani women through cyberspace technology; Rukhsana Arshad -- 16. Towards social inclusion: creating change through a community-developed model of Person-Centred Reviews (PCRs) to support children with Special Educational Needs and Disabilities (SEND); Nick Hammond, Nicola Palmer -- 17. Overcoming marginalisation and mental distress through community supported agriculture: the Streccapogn experience in Monteveglio, Italy; Anna Zoli, Jacqueline Akhurst, Di Martino, S., Bochicchio, D. -- 18. Community-based service learning during clinical psychology training: working at the critically reflective interface; Jacqueline Akhurst, Carol Mitchell -- 19. Health Inequities of Silent Roma Ranks from a Social Justice Perspective; Daniela E. Miranda, Marta Escobar-Ballesta, Emilio Vizarraga-Trigueros, Maria-Jesús Albar, Manuel Garcia-Ramirez -- 20. 'I am not disabled, I just need some help': Are Critical Community Psychology approaches a promising way to engage with people with learning disabilities?; Michael Richards -- 21. Marginalised Youth Navigating Uncertainty: Reflections on co-construction and methodology in Nepal; Vicky Johnson, Andy West, Sumon Kamal Tuladhar, Shubhendra Man Shrestha, Sabitra Neupane -- 22. Finding safety in trauma recovery at a South African state care centre for abused and neglected youth ; Sharon Johnson -- 23. Collaborating with Social Justice Activists in Ghana's Fight Against Modern Day Slavery: A Case Study of Challenging Heights; Kate Danvers -- 24. Community Based Participatory Research (CBPR) as an emancipatory modality promoting social transformation, empowerment, agency, and activism; Naiema Taliep, Samed Bulbulia, Sandy Lazarus, Mohamed Seedat and Building Bridges Team -- 25. The value of togetherness across cultures; Kelly Price, Hayley Higson, Ndumanene Devlin Silungwe -- 26. Linking space, place, and relational wellbeing in co-productive ways; Jenny Fisher, Rebecca Lawthom, Leanne Rimmer, Andrew Stevenson and The Manchester Street Poem Collective -- 27. Mediating the effects of austerity with creativity, compassion and community based approaches; Hayley Higson, Ste Weatherhead, Suzanne Hodge, H Williams -- 28. Writing stories of and from the future: Fostering personal and socio-political action; Nicholas Wood, Anneke Sools -- 29. The Legacy of Art Making: agency, activism and finding the world; Olivia Sagan -- 30. We tell our own stories: Older adults as expert researchers; Erin Elizabeth Partridge, The Elder Care Alliance -- 31. "We can speak but will there be any change?" Voices from Blikkiesdorp, South Africa; Rashid Ahmed, Abdulrazak Karriem, Shaheed Mohammed -- 32. Conclusion; Carl Walker, Sally Zlotowitz, Anna Zoli.
Keywords: Community psychology; Clinical psychology; Critical psychology; Mental health; Social policy; Social psychology; Community Psychology; Clinical Psychology; Critical Psychology; Mental Health; Social Policy; Social Psychology